Nepal’s growing dependency on food imports: A threat to national sovereignty and ways forward - Adhikari, Jagannath; Shrestha, Milan; Paudel, Dinesh (Nepal Public Policy Review, 2021)
Nepal's food imports are growing at an alarming rate. Recent reports suggest a 65% jump in the imports of the key agricultural products between 2015 to 2020. It signals not only the growing dependency trends but also raises serious questions about the future of the agricultural sector in the country–a potential threat to national security and sovereignty. While the topic receives regular media coverage, rarely examined are the historical contexts and the socio-economic, (geo)-political, and cultural drivers of the growing dependency on food imports. Using a political economy approach, we take a systematic look at the food production and import trajectories along with a set of historically important internal and external factors affecting Nepal's food systems. The main objective of this paper is to examine how Nepal became a net food importer in recent decades and discuss some potential ways forward. We argue that while the sharp rise in food imports is unprecedented for Nepal's historically agriculture-based economy, it is hardly surprising in a globalized world; it is emblematic of the global decline of subsistence agriculture in the face of the wider market economy. We conclude that the changes in Nepal's food production and import trajectories are largely influenced by four key interconnected endogenous and exogenous drivers: 1) the politics of modernization and economic growth affecting the agriculture and food systems, 2) regional geopolitics and increasing economic/market dependence, 3) ineffective government policies on food production and imports, and 4) political instability and insurgency forcing migration and off-farm incomes.